EKSISTENSI KERAJINAN BATIK TULIS ( STUDI PERKEMBANGAN DAN DAMPAK SOSIAL EKONOMI MASYARAKAT DESA KEBON, KECAMATAN BAYAT, KABUPATEN KLATEN) - Rahayu, Puji (Candi)
ABSTRACT   Puji Rahayu. EXISTENCE OF BATIK TULIS CRAFT (Development Studies and Socio-Economic Impact of Rural Community Kebon, Bayat district, Klaten). Thesis. Surakarta: Teacher training and education faculty in Sebelas Maret University. July 2012. The aim of this study is to determine: (1) the development of Batik Tulis production in the Kebon village, (2) market network system of batik tulis craft in the Kebon village, (3) the influence of Batik Tulis craft for social and economic life of the villagers Kebon. The methodology of this research was qualitative descriptive. On this research used a single fixed case study which the object would be observed has limited and centralized on certain location which has special characteristics. The data sources used were the source object, places, events, informants and documents. The technique of collecting data used were observation, interviews, and documents analysis. The technique of sampling used was purposive sampling is getting sampling based on the purpose of the research, the place where the researcher choose informant  who know the issues deeply and can be trusted. In this research used two triangulation techniques to find out the validity of the data namely triangulation data and triangulation method. Technique of analyzing data used was interactive analysis which the analysis process that moves between three components there was data reduction, data presentation and verification or inference which took place in a cycle. Based on this research can be concluded that: (1) the development of  batik tulis production in Kebon village since 2007, its production process is still using the traditional way, using the coloring and motifs of nature (2) market network system of the batik tulis craft to Semarang, Yogyakarta and Jakarta and marketed through exhibitions and internet (3) the existence of batik tulis craft in the Kebon village bring influence to the surrounding community, namely the influence of the social field, such as adding a good relationship between citizens and the changing social status of the unemployed become crafters. While the economy is able to increase income and welfare.